2006
DOI: 10.1016/j.molcata.2006.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization mechanism of TiO2 on flexible fluorocarbon films as a functional photocatalyst

Abstract: The repetitive discoloration kinetics of the azo-dye Methyl Orange (taken as a model organic compound) was followed under solar simulated radiation (90 mW/cm 2 ) to assess the performance of the TiO 2 /Tedlar ® composite photocatalyst. The influence of solution parameters on the photo-discoloration process: pH, dye concentration, applied light intensity and concentration of H 2 O 2 were systematically investigated. During the photocatalysis a modification occurs in the TiO 2 /Tedlar ® composite due to the TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The half reaction and total decay times of MO in our experiments are comparable to literature data for tests carried out with the catalyst suspended in the liquid-phase , under comparable operating conditions. In our case, in fact, the molar ratio TiO 2 /substrate was pretty low (≈2) if compared to the mentioned literature data where the above ratio was 2 or 3 orders of magnitude higher, thus leading to a higher involvement of the catalyst.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The half reaction and total decay times of MO in our experiments are comparable to literature data for tests carried out with the catalyst suspended in the liquid-phase , under comparable operating conditions. In our case, in fact, the molar ratio TiO 2 /substrate was pretty low (≈2) if compared to the mentioned literature data where the above ratio was 2 or 3 orders of magnitude higher, thus leading to a higher involvement of the catalyst.…”
Section: Resultssupporting
confidence: 86%
“…In our case, in fact, the molar ratio TiO 2 /substrate was pretty low (≈2) if compared to the mentioned literature data where the above ratio was 2 or 3 orders of magnitude higher, thus leading to a higher involvement of the catalyst. In all cases literature data consisted of nanostructured semiconductor suspensions with average particle size 1 order of magnitude lower than the particles used in present work (higher specific surface). , …”
Section: Resultsmentioning
confidence: 97%
“…A new peak at around 687.1 eV emerged in addition to the peak at 688.0 eV. The peak at 687.1 eV may stem from the fluorine atoms adjacent to the carboxylic acid, which would interact with the TiO 2 surface . From the collective results of the surface coverage, FTIR, and XPS measurements, the adsorption geometries of ZnPH and ZnPF on the TiO 2 surface are proposed.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, based on the porphyrin densities adsorbed on the TiO 2 film, dye-loading experiments, and estimation of the corresponding surface coverage for each dyes, ZnPF was found to achieve much lower surface coverage than ZnPH (Γ = 6.2 × 10 –11 and 15 × 10 –11 mol·cm –2 , respectively). To explain such difference of behavior, the authors suggested the possible existence of additional interactions between fluorine atoms of ZnPF and TiO 2 . Despite lower surface coverage of ZnPF than ZnPH , the LHE values of the TiO 2 / ZnPF +CDCA and TiO 2 / ZnPH +CDCA cells were comparable, considering the effect of the light-scattering TiO 2 layer.…”
Section: Trans-a2bc-type Design For Meso-substituted Porphyrin Dyes: ...mentioning
confidence: 99%